Intravenous Lidocaine for Acute Pain: A Single-Institution Retrospective Study - Kyle De Oliveira; Naveen Eipe (Adis, Springer Healthcare, 2020)
Abstract Background In the perioperative period, intravenous lidocaine has been used as an opioid-sparing systemic analgesic with additional anti-inflammatory and anti-hyperalgesic properties. Objective The aim of this retrospective study was to review the utilization, efficacy, and safety of intravenous lidocaine on our Acute Pain Service (APS) and identify surgical and patient populations where this intervention was found to be useful. Patients and Methods This retrospective study was designed to assess acute pain management in patients who received an intravenous lidocaine infusion between February 2013 and December 2017. Data collected included demographics, surgery type, infusion duration, pain scores, analgesic consumption, and adverse effects. Pain scores included rest and active pain scores and were analyzed by surgical model and subgroups. Clinically important differences (CIDs) in pain were determined by changes in pain score difference of ≥ 2 (11-point scale) or ≥ 30% reduction in pain intensity. A patient was considered to have a true CID if a CID was observed with rest and/or active pain scores at both first to second (4-24 h) and first to final time point (4 h to infusion end) comparisons. Results In total, 544 patients received intravenous lidocaine during this period, and 394 were included in the final analysis. The average (± standard deviation) duration of infusion was 68.60 ± 49.52 h. Surgical specialties included gastrointestinal surgery (41%), orthopedics (28%), neurosurgery (15%), vascular surgery (10%), and others (6%). Overall, 56.1% of the study population experienced a CID, with reduced pain scores at rest and/or with activity. CIDs were also observed in patients with chronic pain (53.5%) and when intravenous lidocaine was used as a rescue technique (69.6%). Within the rescue cohort, opioid-dependent and opioid-naïve patients experienced 23.0% and 45.6% reductions, respectively, in their 8-h intravenous opioid consumption. In total, 37 patients in the study experienced transient signs of mild local anesthetic toxicity, which resolved with infusion titration (conservative) management. One serious adverse event required intervention, and the patient was successfully resuscitated. Conclusions This retrospective study at a single institution with an APS policy for intravenous lidocaine in the postoperative period identifies benefits of intravenous lidocaine in certain surgical and patient populations. The findings need to be confirmed with further research.